Long noncoding RNA DHRS4 antisense RNA 1 suppresses osteosarcoma cell proliferation and promotes apoptosis through a competitive endogenous RNA mechanism - Zhouzhou Tang; Zhihao Li; Guofeng Wu; Jianjun Li; Jianye Tan; Lixin Zhu (Scientific Reports)
Abstract Osteosarcoma (OS) is the most common primary malignant bone tumor. Recent evidence suggests that the novel long noncoding RNA DHRS4 antisense RNA 1 (DHRS4-AS1) serves an important role in cancer progression and metastasis. However, its function and molecular mechanism in OS remain largely unknown. In the present study, DHRS4-AS1 expression was detected in OS cells by quantitative PCR. Gain- and loss-of-function experiments were conducted to study the effects of DHRS4-AS1 on the proliferation and apoptosis of OS cells. The potential mechanism of DHRS4-AS1 was examined through bioinformatics analysis and rescue experiments. DHRS4-AS1 was downregulated in OS cell lines. DHRS4-AS1 depletion promoted proliferation and inhibited apoptosis in OS cells, whereas DHRS4-AS1 overexpression had the opposite effects. Further research suggested that DHRS4-AS1 inhibited OS progression by regulating the microRNA-362-5p/aminopeptidase puromycin sensitive axis. The present findings suggested that DHRS4-AS1 may serve as a potential therapeutic target for OS.